Digital Economy and Health: A Case Study of a Leading Enterprise's Value Mining Mode in the Global Big Health Market - Guan, Jialin; Xu, Huijuan; Wang, Yunfeng; Ma, Yaoguang; Wang, Yu; Gao, Rui; Yu, Kexuan (Frontiers in Public Health, 2022)
The Coronavirus Disease (COVID-19) swept the world and posed a serious threat to human health. Health and elderly care enterprises are committed to continuously improving people's health. With the rapid development of digital economy, many enterprises has established product-service digital ecosystem after combining “Internet +”, big data, cloud computing and big-health industry. This paper uses the case study method to analyze the overseas market value mining mode of health and elderly care enterprises through in-depth research on the leading enterprise of smart health and elderly care. This study explores the global big-health market value mining mode of the leading enterprise by cluster analysis and Bayesian model with the support of data of geographical characteristics, users’ sleep habits and national big health. This study provides new ideas for the overseas market value mining model of other health and elderly care enterprises.